Development of the medicine safety data monitoring system GERMES PV (literature monitoring and internet sources) - Chadiuk, A.V.; Mashkovskyi, S.S. (Інститут програмних систем НАН України, 2024)
The global coronavirus pandemic of recent years has led to an emergency situation in the field of health care, determined the need to develop new vaccines for the treatment of the population under the guidance of the World Health Organization. Assessment of the safety and effectiveness of the use of these vaccines requires a wide range of research, one of the methods of which is literature monitoring of scientific publications. Significant labor costs for the search and analysis of articles make the creation and implementation of computer information and search systems for monitoring literature and Internet sources an urgent issue. Developed for this purpose, the medicine safety data monitoring system Germes PV is intended for the comprehensive application of modern technologies of automated monitoring of periodicals and Internet resources (web portals, websites, electronic libraries, etc.) in order to search for publications on the safety of drugs, availability adverse reactions and lack of effectiveness of medicinal products, feedback and suggestions of interested persons and other information in the field of pharmacovigilance. In this work, a comprehensive analysis of the subject area is carried out and ways of automating the activities of health care institutions and pharmaceutical companies in this area are described.Prombles in programming 2024; 2-3: 190-198